2017
DOI: 10.4186/ej.2017.21.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies of NF and RO Membranes on Pharmaceutical Removal and Membrane Fouling Effects

Abstract: The efficiencies of nanofiltration (NF) and reverse osmosis (RO) membranes in removing carbamazepine (CBZ) and sulfamethoxazole (SMX) were studied. To do this, the NF and RO membranes NF-1 and RO-1 were used, and the isoelectric points of the NF-1 and RO-1 membranes were determined to be at approximate pH of 6.0. The NF-1 membrane's CBZ rejections at solution pH values of 5.0, 6.0, and 7.0 were in a slight range of 92-93%. Additionally, SMX rejections by the NF-1 membrane at the same three solution pH values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Generally, solid-phase adsorption and oxidation methods have been primarily used in physical and chemical SMX removal processes, respectively. Phadunghus et al found that the removal rate of SMX by nanofiltration and reverse osmosis membrane separation technology could reach 94–98% ( 16 ). Yazdanbakhsh et al used the Mn-WO 3 /LED photocatalytic system to degrade SMX in wastewater, with a removal rate of up to 85% in 3 h ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, solid-phase adsorption and oxidation methods have been primarily used in physical and chemical SMX removal processes, respectively. Phadunghus et al found that the removal rate of SMX by nanofiltration and reverse osmosis membrane separation technology could reach 94–98% ( 16 ). Yazdanbakhsh et al used the Mn-WO 3 /LED photocatalytic system to degrade SMX in wastewater, with a removal rate of up to 85% in 3 h ( 17 ).…”
Section: Introductionmentioning
confidence: 99%